PENGARUH TEKNIK MOTIVASI GURU DAN METODE PEMBELAJARAN TERHADAP AKHLAK SISWA DI MTs. MA’ARIF ROUDLOTUT-THOLIBIN PURWOSARI METRO UTARA - Muhammad Rudi Wijaya (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
Attitude is the soul from Islamic education, For the purpose of Islamic education is to educate people that having a generous attitude. Attitude is established through formal education in the learning process. So that a teacher is expected to deliver it to be maximized in any learning. The results showed that the technique prasurvei motivation and methods of learning had taken but there is an obligation on bad students.Through technical innovation is given by a tutor and methods of learning attitude optimally expected students could be achieved in full. Thus the purpose of learning for good. The study aimed to identify the technique teacher motivation for students, attitude the learning methods he continued to influence on this fact attitude as well as teacher motivation techniques and methods of learning attitude. Including the design of this research. quantitative research using multiple. the regression equation is linearPopulation in this study were those coming Madrasah Tsanawiyah Ma’arif Roudlotut Tholibin Purwosari south metro With the number of 136. The sampling technique uses proportional strataied sampling technique. With a sample of 29 students. Data collection in the study using questionnaire and documentation instruments. Based on the results of the data analysis, it was found that there was a significant influence of the teacher's motivation technique on student morals by 80.7% with a linear regression equation Y = 7,866+0,957 X1, the influence of learning methods on student morals is 71.1% with linear regression equations Ŷ= 5,861 + 0,958 X2, and the joint influence between motivation techniques and learning methods on student morals is 79.7% with linear regression equations  Ŷ= 6,059 + 0,804(X1)+ 0,179(X2). This means that students will be better to minimize the moral motivation techniques conducted by teachers through the learning process carried out very good, so are. learning methods Moral students would be better off if the learning methods he continued. implemented and properly applied